Concerted evolution of class I genes in the major histocompatibility complex of murine rodents. - Rada, C (1990)
Full-length cDNA sequences of two class I major histocompatibility complex molecules from the DA strain of Rattus norvegicus are reported. One codes for the classical class I restriction element RT1.Aa, which maps to the locus in the rat major histocompatibility complex homologous to H-2K in the mouse. The other probably codes for a soluble nonclassical class I molecule present in DA rat serum; a short deletion in the fifth exon implies that the translated product will terminate in the membrane-spanning region. These sequences have been compared with mouse classical class I sequences as well as with three published rat class I cDNA partial sequences. The results show, first, that "locus-specific" substitutions from the H-2K, H-2D, and H-2L data set are scrambled in the RT1.Aa molecule; a majority of these substitutions have H-2D/L-specific features. Second, the data show that the four rat sequences are strikingly similar to one another regardless of locus or haplotype of origin; they share a number of apparently species-specific features that distinguish them all from mouse classical class I sequences, which likewise share distinctive features of their own. The results suggest that segmental sequence exchange plays a major role in determining the evolution of sequence in class I major histocompatibility complex molecules.